Écrire sur la Shoah avant la Shoah : notes sur Kafka et Levi - Luca De Angelis (Laboratoire Italien)
The number of Jewish writers, especially during the twenty years between the two wars, was not insignificant. It was they who heeded the warnings of their instincts and scrutinised the underground and telluric movements of history; as these looming sensations of danger increased, these feelings were then poured into the literary space. Franz Kafka, in particular, comes to mind. Identifying the Prague writer as an avant-goût, a gloomy foreboding of what would befall the Jews, was a small cohort of readers who were neither easily impressionable nor fatuous. Among these was Primo Levi. Even though he did not consider Kafka “quite the same”, the Turin writer accepted the invitation to translate The Trial. In his opinion, even though Kafka was “writing in the first decades of this century, at the turn of the First World War, he foresaw many things”. Thanks to a tremendous imaginative force, in the midst of so many “confused signals”, Kafka had foretold, among other things, the inhumanity of Auschwitz. Levi considered Kafka a prophet of the Holocaust. Even though he did not go to Auschwitz, it was as if he had been able to foretell it “with a clairvoyance that amazes and wounds like blinding light”.